Improvement of Foreign Exchange Risk Management in Tourism and Hospitality Industry Enterprises - Skabeeva, Larisa; Shaliapina, Marina; Panova, Nataliia; Nikolskaya, Elena; Lebedeva, Olga (Anais Brasileiros de Estudos Turísticos, 2022)
The study takes a look at the approaches to the foreign exchange risk management of tourism and hospitality industry enterprises as the expansion of foreign economic activity requires improving the efficiency of managing such risks. Transfer pricing is considered one of the most effective methods for regulating foreign exchange risk. The conceptual principles of foreign exchange risk management are developed with consideration of the place and goals of an enterprise in the tourism and hospitality industry, as well as the features of the internal and external environments, that create the prerequisites for increasing the efficiency of the organizational and economic mechanism. It is concluded that approaches to developing a program to improve the efficiency of managing risks under study determine the optimal combination of organizational and software-integrated aspects that reduce the level of risk to the optimum, given a steady increase in competitiveness and profitability.